Criação de um material auxiliar para o ensino da língua japonesa aos alunos do 8° e 9° ano da Escola Professora Josephina de Mello - Miura, Ellen Yurika (Brasil, 2022)
The present research aimed to develop and analyze a support material that could be used as a playful tool to improve the learning of students at Escola Professora Josephina de Mello and help them to achieve a significant learning of Japanese language content. As a theoretical foundation, the theory of meaningful learning by David Ausubel (MOREIRA, 1999) was used and research was carried out on the use of games and recreational activities in the teaching of foreign languages. The sugoroku board game was applied in class 3A of the 8th and 9th grade during the year 2020, as a form of review for the written tests carried out at the school and the grades obtained by the students were analyzed qualitatively and quantitatively, obtaining a result satisfactory in terms of learning the Japanese language.